Martin Escardo.

Excluded middle related things. Notice that this file doesn't
postulate excluded middle. It only defines what the principle of
excluded middle is.

In the Curry-Howard interpretation, excluded middle say that every
type has an inhabitant or os empty. In univalent foundations, where
one works with propositions as subsingletons, excluded middle is the
principle that every subsingleton type is inhabited or empty.

\begin{code}

{-# OPTIONS --safe --without-K #-}

module UF.ClassicalLogic where

open import MLTT.Spartan

open import UF.Base
open import UF.Equiv
open import UF.FunExt
open import UF.PropTrunc
open import UF.Subsingletons
open import UF.Subsingletons-FunExt
open import UF.SubtypeClassifier
open import UF.UniverseEmbedding

\end{code}

Excluded middle (EM) is not provable or disprovable. However, we do
have that there is no truth value other than false (⊥) or true (⊤),
which we refer to as the density of the decidable truth values.

\begin{code}

EM :  𝓤  𝓤  ̇
EM 𝓤 = (P : 𝓤 ̇ )  is-prop P  P + ¬ P

excluded-middle = EM

lower-EM :  𝓥  EM (𝓤  𝓥)  EM 𝓤
lower-EM 𝓥 em P P-is-prop = f d
 where
  d : Lift 𝓥 P + ¬ Lift 𝓥 P
  d = em (Lift 𝓥 P) (equiv-to-prop (Lift-is-universe-embedding 𝓥 P) P-is-prop)

  f : Lift 𝓥 P + ¬ Lift 𝓥 P  P + ¬ P
  f (inl p) = inl (lower p)
  f (inr ν) = inr  p  ν (lift 𝓥 p))

Excluded-Middle : 𝓤ω
Excluded-Middle =  {𝓤}  EM 𝓤

EM-is-prop : FunExt  is-prop (EM 𝓤)
EM-is-prop {𝓤} fe = Π₂-is-prop
                      {𝓤} {𝓥}  fe 𝓤 𝓥)
                      _  decidability-of-prop-is-prop (fe 𝓤 𝓤₀))

LEM :  𝓤  𝓤  ̇
LEM 𝓤 = (p : Ω 𝓤)  p holds + ¬ (p holds)

EM-gives-LEM : EM 𝓤  LEM 𝓤
EM-gives-LEM em p = em (p holds) (holds-is-prop p)

LEM-gives-EM : LEM 𝓤  EM 𝓤
LEM-gives-EM lem P i = lem (P , i)

\end{code}

Added by Martin Escardo and Tom de Jong 29th August 2024. Originally
we worked with what is now called WEM'. But it turns out that it is
not necessary to assume that P is a proposition, and so we now work
with the new definition WEM, which removes this assumption.

\begin{code}

WEM' :  𝓤  𝓤  ̇
WEM' 𝓤 = (P : 𝓤 ̇ )  is-prop P  ¬ P + ¬¬ P

WEM :  𝓤  𝓤  ̇
WEM 𝓤 = (P : 𝓤 ̇ )  ¬ P + ¬¬ P

WEM'-gives-WEM : funext 𝓤 𝓤₀  WEM' 𝓤  WEM 𝓤
WEM'-gives-WEM fe wem' P =
 Cases (wem' (¬ P) (negations-are-props fe)) inr (inl  three-negations-imply-one)

WEM-gives-WEM' : WEM 𝓤  WEM' 𝓤
WEM-gives-WEM' wem P P-is-prop = wem P

WEM-is-prop : FunExt  is-prop (WEM 𝓤)
WEM-is-prop {𝓤} fe = Π-is-prop (fe (𝓤 ) 𝓤)
                        _  decidability-of-prop-is-prop (fe 𝓤 𝓤₀)
                               (negations-are-props (fe 𝓤 𝓤₀)))

WEM'-is-prop : FunExt  is-prop (WEM' 𝓤)
WEM'-is-prop {𝓤} fe = Π₂-is-prop  {𝓥} {𝓦}  fe 𝓥 𝓦)
                        _ _  decidability-of-prop-is-prop (fe 𝓤 𝓤₀)
                                 (negations-are-props (fe 𝓤 𝓤₀)))

\end{code}

Double negation elimination is equivalent to excluded middle.

\begin{code}

DNE :  𝓤  𝓤  ̇
DNE 𝓤 = (P : 𝓤 ̇ )  is-prop P  ¬¬ P  P

EM-gives-DNE : EM 𝓤  DNE 𝓤
EM-gives-DNE em P i φ = cases id  u  𝟘-elim (φ u)) (em P i)

double-negation-elim : EM 𝓤  DNE 𝓤
double-negation-elim = EM-gives-DNE

fake-¬¬-EM : {X : 𝓤 ̇ }  ¬¬ (X + ¬ X)
fake-¬¬-EM u = u (inr  p  u (inl p)))

DNE-gives-EM : funext 𝓤 𝓤₀  DNE 𝓤  EM 𝓤
DNE-gives-EM fe dne P isp = dne (P + ¬ P)
                             (decidability-of-prop-is-prop fe isp)
                             fake-¬¬-EM

all-props-negative-gives-DNE : funext 𝓤 𝓤₀
                             ((P : 𝓤 ̇ )  is-prop P  Σ Q  𝓤 ̇ , (P  ¬ Q))
                             DNE 𝓤
all-props-negative-gives-DNE {𝓤} fe ϕ P P-is-prop = I (ϕ P P-is-prop)
 where
  I : (Σ Q  𝓤 ̇ , (P  ¬ Q))  ¬¬ P  P
  I (Q , f , g) ν = g (three-negations-imply-one (double-contrapositive f ν))

all-props-negative-gives-EM
 : funext 𝓤 𝓤₀
  ((P : 𝓤 ̇ )  is-prop P  Σ Q  𝓤 ̇ , (P  ¬ Q))
  EM 𝓤
all-props-negative-gives-EM {𝓤} fe ϕ
 = DNE-gives-EM fe (all-props-negative-gives-DNE fe ϕ)

fe-and-em-give-propositional-truncations
 : FunExt
  Excluded-Middle
  propositional-truncations-exist
fe-and-em-give-propositional-truncations fe em =
 record {
  ∥_∥          = λ X  ¬¬ X ;
  ∥∥-is-prop   = Π-is-prop (fe _ _)  _  𝟘-is-prop) ;
  ∣_∣          = λ x u  u x ;
  ∥∥-rec       = λ i u φ  EM-gives-DNE em _ i (¬¬-functor u φ)
  }

\end{code}

Like WEM, we don't need to assume that P and Q are propositions in the
definition of De Morgan's Law (added by Martin Escardo and Tom de Jong
29th August 2024). See below for a proof. But we begin with a
definition that does.

\begin{code}

De-Morgan :  𝓤  𝓤  ̇
De-Morgan 𝓤 = (P Q : 𝓤 ̇ )
              is-prop P
              is-prop Q
              ¬ (P × Q)  ¬ P + ¬ Q

EM-gives-De-Morgan : EM 𝓤
                    De-Morgan 𝓤
EM-gives-De-Morgan em A B i j =
 λ (ν : ¬ (A × B)) 
      Cases (em A i)
        (a : A)  Cases (em B j)
                      (b : B)  𝟘-elim (ν (a , b)))
                     inr)
       inl

\end{code}

But already weak excluded middle gives De Morgan:

\begin{code}

non-contradiction : {X : 𝓤 ̇ }  ¬ (X × ¬ X)
non-contradiction (x , ν) = ν x

De-Morgan' :  𝓤  𝓤  ̇
De-Morgan' 𝓤 = (P Q : 𝓤 ̇ )  ¬ (P × Q)  ¬ P + ¬ Q

De-Morgan'-gives-De-Morgan : De-Morgan' 𝓤  De-Morgan 𝓤
De-Morgan'-gives-De-Morgan d' P Q i j = d' P Q

WEM-gives-De-Morgan' : WEM 𝓤  De-Morgan' 𝓤
WEM-gives-De-Morgan' wem A B =
 λ (ν : ¬ (A × B)) 
      Cases (wem A)
       inl
        (ϕ : ¬¬ A)
              Cases (wem B)
                inr
                 (γ : ¬¬ B)  𝟘-elim
                                 (ϕ  (a : A)  γ  (b : B)  ν (a , b))))))

WEM-gives-De-Morgan : WEM 𝓤  De-Morgan 𝓤
WEM-gives-De-Morgan = De-Morgan'-gives-De-Morgan  WEM-gives-De-Morgan'

De-Morgan-gives-WEM : funext 𝓤 𝓤₀  De-Morgan 𝓤  WEM 𝓤
De-Morgan-gives-WEM fe d =
 WEM'-gives-WEM fe
   P i  d P (¬ P) i (negations-are-props fe) non-contradiction)

De-Morgan-gives-De-Morgan' : funext 𝓤 𝓤₀  De-Morgan 𝓤  De-Morgan' 𝓤
De-Morgan-gives-De-Morgan' fe = WEM-gives-De-Morgan'  De-Morgan-gives-WEM fe

\end{code}

Is the above untruncated De Morgan Law a proposition? Not in
general. If it doesn't hold, it is vacuously a proposition. But if it
does hold, it is not a proposition. We prove this by modifying any
given δ : De-Mordan 𝓤 to a different δ' : De-Morgan 𝓤. Then we also
consider a truncated version of De-Morgan that is a proposition and is
logically equivalent to De-Morgan. So De-Morgan 𝓤 is not necessarily a
proposition, but it always has split support (it has a proposition as
a retract).

\begin{code}

De-Morgan-is-prop : ¬ De-Morgan 𝓤  is-prop (De-Morgan 𝓤)
De-Morgan-is-prop ν δ = 𝟘-elim (ν δ)

De-Morgan-is-not-prop : funext 𝓤 𝓤₀  De-Morgan 𝓤  ¬ is-prop (De-Morgan 𝓤)
De-Morgan-is-not-prop {𝓤} fe δ = IV
 where
  open import MLTT.Plus-Properties

  wem : WEM 𝓤
  wem = De-Morgan-gives-WEM fe δ

  g : (P Q : 𝓤 ̇ )
      (i : is-prop P) (j : is-prop Q)
      (ν : ¬ (P × Q))
      (a : ¬ P + ¬¬ P)
      (b : ¬ Q + ¬¬ Q)
      (c : ¬ P + ¬ Q)
     ¬ P + ¬ Q
  g P Q i j ν (inl _) (inl v) (inl _) = inr v
  g P Q i j ν (inl u) (inl _) (inr _) = inl u
  g P Q i j ν (inl _) (inr _) _       = δ P Q i j ν
  g P Q i j ν (inr _) _       _       = δ P Q i j ν

  δ' : De-Morgan 𝓤
  δ' P Q i j ν = g P Q i j ν (wem P) (wem Q) (δ P Q i j ν)

  I : (i : is-prop 𝟘) (h : ¬ 𝟘)  wem 𝟘  inl h
  I i h = I₀ (wem 𝟘) refl
   where
    I₀ : (a : ¬ 𝟘 + ¬¬ 𝟘)  wem 𝟘  a  wem 𝟘  inl h
    I₀ (inl u) p = transport  -  wem 𝟘  inl -) (negations-are-props fe u h) p
    I₀ (inr ϕ) p = 𝟘-elim (ϕ h)

  ν : ¬ (𝟘 × 𝟘)
  ν (p , q) = 𝟘-elim p

  II : (i j : is-prop 𝟘)  δ' 𝟘 𝟘 i j ν  δ 𝟘 𝟘 i j ν
  II i j = II₃
   where
    m n : ¬ 𝟘 + ¬ 𝟘
    m = δ 𝟘 𝟘 i j ν
    n = g 𝟘 𝟘 i j ν (inl 𝟘-elim) (inl 𝟘-elim) m

    II₁ : δ' 𝟘 𝟘 i j ν  n
    II₁ = ap₂  -₁ -₂  g 𝟘 𝟘 i j ν -₁ -₂ m)
              (I i 𝟘-elim)
              (I j 𝟘-elim)

    II₂ : (m' : ¬ 𝟘 + ¬ 𝟘)
         m  m'
         g 𝟘 𝟘 i j ν (inl 𝟘-elim) (inl 𝟘-elim) m'  m
    II₂ (inl x) p q = +disjoint
                       (inl x      =⟨ p ⁻¹ 
                        m          =⟨ q ⁻¹ 
                        inr 𝟘-elim )
    II₂ (inr x) p q = +disjoint
                       (inl 𝟘-elim =⟨ q 
                        m          =⟨ p 
                        inr x      )

    II₃ : δ' 𝟘 𝟘 i j ν  m
    II₃ = transport (_≠ m) (II₁ ⁻¹) (II₂ m refl)

  III : δ'  δ
  III e = II 𝟘-is-prop 𝟘-is-prop III₀
   where
    III₀ : δ' 𝟘 𝟘 𝟘-is-prop 𝟘-is-prop ν  δ 𝟘 𝟘 𝟘-is-prop 𝟘-is-prop ν
    III₀ = ap  -  - 𝟘 𝟘 𝟘-is-prop 𝟘-is-prop ν) e

  IV : ¬ is-prop (De-Morgan 𝓤)
  IV i = III (i δ' δ)

De-Morgan-curiousity : funext 𝓤 𝓤₀
                      ¬¬ is-prop (De-Morgan 𝓤)
                      is-prop (De-Morgan 𝓤)
De-Morgan-curiousity fe =
 De-Morgan-is-prop  contrapositive (De-Morgan-is-not-prop fe)

module _ (pt : propositional-truncations-exist) where

 open PropositionalTruncation pt

 truncated-De-Morgan :  𝓤  𝓤  ̇
 truncated-De-Morgan 𝓤 = (P Q : 𝓤 ̇ )  ¬ (P × Q)  ¬ P  ¬ Q

 truncated-De-Morgan' :  𝓤  𝓤  ̇
 truncated-De-Morgan' 𝓤 = (P Q : 𝓤 ̇ )
                         is-prop P
                         is-prop Q
                         ¬ (P × Q)  ¬ P  ¬ Q

 truncated-De-Morgan-is-prop : FunExt  is-prop (truncated-De-Morgan 𝓤)
 truncated-De-Morgan-is-prop fe = Π₃-is-prop  {𝓤} {𝓥}  fe 𝓤 𝓥)
                                    P Q ν  ∨-is-prop)

 truncated-De-Morgan'-is-prop : FunExt  is-prop (truncated-De-Morgan' 𝓤)
 truncated-De-Morgan'-is-prop fe = Π₅-is-prop  {𝓤} {𝓥}  fe 𝓤 𝓥)
                                     P Q i j ν  ∨-is-prop)

 De-Morgan-gives-truncated-De-Morgan' : De-Morgan 𝓤  truncated-De-Morgan' 𝓤
 De-Morgan-gives-truncated-De-Morgan' d P Q i j ν =  d P Q i j ν 

 truncated-De-Morgan'-gives-WEM' : funext 𝓤 𝓤₀  truncated-De-Morgan' 𝓤  WEM' 𝓤
 truncated-De-Morgan'-gives-WEM' {𝓤} fe t P i = III
  where
   I : ¬ (P × ¬ P)  ¬ P  ¬¬ P
   I = t P (¬ P) i (negations-are-props fe)

   II : ¬ P  ¬¬ P
   II = I non-contradiction

   III : ¬ P + ¬¬ P
   III = exit-∥∥
          (decidability-of-prop-is-prop fe
          (negations-are-props fe))
          II

 truncated-De-Morgan'-gives-WEM : funext 𝓤 𝓤₀  truncated-De-Morgan' 𝓤  WEM 𝓤
 truncated-De-Morgan'-gives-WEM {𝓤} fe =
  WEM'-gives-WEM fe  truncated-De-Morgan'-gives-WEM' fe

 truncated-De-Morgan'-gives-De-Morgan : funext 𝓤 𝓤₀  truncated-De-Morgan' 𝓤  De-Morgan 𝓤
 truncated-De-Morgan'-gives-De-Morgan fe t P Q i j ν =
  WEM-gives-De-Morgan (truncated-De-Morgan'-gives-WEM fe t) P Q i j ν

 truncated-De-Morgan-gives-truncated-De-Morgan'
  : truncated-De-Morgan 𝓤
   truncated-De-Morgan' 𝓤
 truncated-De-Morgan-gives-truncated-De-Morgan' d P Q i j = d P Q

 truncated-De-Morgan'-gives-truncated-De-Morgan
  : funext 𝓤 𝓤₀
   truncated-De-Morgan' 𝓤
   truncated-De-Morgan 𝓤
 truncated-De-Morgan'-gives-truncated-De-Morgan {𝓤} fe d P Q ν
  =  WEM-gives-De-Morgan' (truncated-De-Morgan'-gives-WEM fe d) P Q ν 

\end{code}

The above shows that weak excluded middle, De Morgan and truncated De
Morgan are logically equivalent, all in their two (primed and
unprimed) versions, so in a total of six logically equivalent
statements.

That weak excluded middle and De Morgan are equivalent is long known
and now part of the folklore. We don't know who proved this first,
but, for example, it is in Johnstone's papers on topos theory and his
Elephant two-volume book.

Mike Shulman asked in the HoTT mailing list [1] whether untruncated De
Morgan implies truncated De Morgan, and Martin Escardo offered a proof
as an answer [2], which Mike Shulman added to the nLab [3].

[1] Mike Shulman. de Morgan's Law.
    https://groups.google.com/g/homotopytypetheory/c/Azq6GVU98II/m/qEp8TeInYgAJ
    1st September 2014.

[3] Martin Escardo. de Morgan's Law.
    https://groups.google.com/g/homotopytypetheory/c/Azq6GVU98II/m/bXMixO9s1boJ
    2nd September 2014

[3] Added to the nLab by Mike Shulman.
    https://ncatlab.org/nlab/show/De%20Morgan%20laws.
    2nd September 2014

Here we have added, to both WEM and De Morgan, truncated or not, the
discussion of whether the types in question need to be propositions or
not for them to be all equivalent, and the answer is that it doesn't
matter whether we assume that the types in question are all
propositions.

\begin{code}

 double-negation-is-truncation-gives-DNE : ((X : 𝓤 ̇ )  ¬¬ X   X )  DNE 𝓤
 double-negation-is-truncation-gives-DNE f P i u = exit-∥∥ i (f P u)

 non-empty-is-inhabited : EM 𝓤  {X : 𝓤 ̇ }  ¬¬ X   X 
 non-empty-is-inhabited em {X} φ =
  cases
    (s :  X )
          s)
    (u : ¬  X )
          𝟘-elim (φ (contrapositive ∣_∣ u))) (em  X  ∥∥-is-prop)

 ¬¬Σ→∃ : {𝓤 𝓣 : Universe} {X : 𝓤 ̇ }  {A : X  𝓣  ̇}  DNE (𝓤  𝓣)  ¬¬ (Σ x  X , A x )  ( x  X , A x)
 ¬¬Σ→∃ {𝓤} {A} {X} {A₁} dn ¬¬Σ = dn _ ∥∥-is-prop (¬¬-functor ∣_∣ ¬¬Σ)

 ∃-not+Π : EM (𝓤  𝓥)
          {X : 𝓤 ̇ }
          (A : X  𝓥 ̇ )
          ((x : X)  is-prop (A x))
          ( x  X , ¬ (A x)) + (Π x  X , A x)
 ∃-not+Π {𝓤} {𝓥} em {X} A is-prop-valued =
  Cases (em ( x  X , ¬ (A x)) ∃-is-prop)
   inl
    (u : ¬ ( x  X , ¬ (A x)))
          inr  (x : X)  EM-gives-DNE
                              (lower-EM (𝓤  𝓥) em)
                              (A x)
                              (is-prop-valued x)
                               (v : ¬ A x)  u  (x , v) )))

 ∃+Π-not : EM (𝓤  𝓥)
          {X : 𝓤 ̇ }
          (A : X  𝓥 ̇ )
          ((x : X)  is-prop (A x))
          ( x  X , A x) + (Π x  X , ¬ (A x))
 ∃+Π-not {𝓤} {𝓥} em {X} A is-prop-valued =
  Cases (em ( x  X , A x) ∃-is-prop)
   inl
    (u : ¬ ( x  X , A x))
          inr  (x : X) (v : A x)  u  x , v ))

 not-Π-implies-∃-not : {X : 𝓤 ̇ } {A : X  𝓥 ̇ }
                      EM (𝓤  𝓥)
                      ((x : X)  is-prop (A x))
                      ¬ ((x : X)  A x)
                       x  X , ¬ A x
 not-Π-implies-∃-not {𝓤} {𝓥} {X} {A} em i f =
  Cases (em E ∃-is-prop)
   id
    (u : ¬ E)
          𝟘-elim (f  (x : X)  EM-gives-DNE
                                    (lower-EM 𝓤 em)
                                    (A x)
                                    (i x)
                                     (v : ¬ A x)  u  x , v ))))
  where
   E =  x  X , ¬ A x

\end{code}

Added by Tom de Jong in August 2021.

\begin{code}

 not-Π-not-implies-∃ : {X : 𝓤 ̇ } {A : X  𝓥 ̇ }
                      EM (𝓤  𝓥)
                      ¬ ((x : X)  ¬ A x)
                       x  X , A x
 not-Π-not-implies-∃ {𝓤} {𝓥} {X} {A} em f = EM-gives-DNE em ( A) ∥∥-is-prop γ
   where
    γ : ¬¬ ( A)
    γ g = f  x a  g  x , a )

\end{code}

Added by Martin Escardo 26th April 2022.

\begin{code}

Global-Choice' :  𝓤  𝓤  ̇
Global-Choice' 𝓤 = (X : 𝓤 ̇ )  is-nonempty X  X

Global-Choice :  𝓤  𝓤  ̇
Global-Choice 𝓤 = (X : 𝓤 ̇ )  X + is-empty X

Global-Choice-gives-Global-Choice' : Global-Choice 𝓤  Global-Choice' 𝓤
Global-Choice-gives-Global-Choice' gc X φ = cases id  u  𝟘-elim (φ u)) (gc X)

Global-Choice'-gives-Global-Choice : Global-Choice' 𝓤  Global-Choice 𝓤
Global-Choice'-gives-Global-Choice gc X = gc (X + ¬ X)
                                              u  u (inr  p  u (inl p))))
\end{code}

TODO. Global choice contradicts univalence. This is already present in
the directory MGS.